The Obstacles in Fulfilling Social Protection for Indonesian Women Migrant Workers in Malaysia from 2016 to 2018 - Alfajri, Ahmad; Maulidia, Halida (Jurnal Hubungan Internasional, 2019)
According to BNP2TKI, Malaysia is the most popular destination country for Indonesian Women Migrant Workers (IWMW), as well as at the top list of IWMW complaints. One of those complaints is regarding the social protection issue. The provision of social protection for IWMW is still limited while it is part of migrant’s rights. The Malaysian government has put some regulations that command its institutions to provide the protections both to its citizens and non-citizens. This study found three big constraints of procuring social protection to IWMW in Malaysia; they were legal barriers, problems in the regulation of Indonesia, and Malaysia immigration policy. In this article, the author analyzed those constraints using feminist theory. This article found that social protection in Malaysia has not fully considered women’s perspectives and experiences while being critical. Furthermore, migration arrangements, both in Indonesia and Malaysia, are also problematic. Those three factors will be discussed in detail using a feminist perspective in looking at the whole problem and the relationship between the patriarchal system and the economy that suppress women.